Freight forecasts - Transport Data Centre (N.S.W.) (Sydney, N.S.W. : Transport Data Centre.)
Spreadsheets contains TDC heavy vehicle freigh forecasts and light commercial vehicle freigh forecasts for 'Expanded' Greater Metropolitan Area (GMA): Sydney Statistical Division, Illawarra Statistical Division, Newcastle Statistical Subdivision and surrounding areas."
Description based on: Feb. 2010.
Title from title screen (viewed on 18 August 2010).
Available via World Wide Web. On 18/08/10 freely available from website of Transport Data Centre at: http://www.transport.nsw.gov.au/tdc/publications.html.
System requirements: Adobe Acrobat Reader to access files in a PDF format.
Selected for archiving
Keywords: Transport Data Centre (N.S.W.) -- Statistics -- Periodicals; Commercial vehicles -- New South Wales -- Illawarra -- Statistics -- Periodicals; Commercial vehicles -- New South Wales -- Newcastle Region -- Statistics -- Periodicals; Commercial vehicles -- New South Wales -- Sydney -- Statistics -- Periodicals; Freight and freightage -- New South Wales -- Illawarra -- Statistics -- Periodicals; Freight and freightage -- New South Wales -- Newcastle Region -- Statistics -- Periodicals; Freight and freightage -- New South Wales -- Sydney -- Statistics -- Periodicals; Trucks -- New South Wales -- Illawarra -- Periodicals -- Periodicals; Trucks -- New South Wales -- Newcastle Region -- Statistics -- Periodicals; Trucks -- New South Wales -- Sydney -- Statistics -- Periodicals